Análise comparativa de características seminais de Mazama cinzas brasileiros: morfometria espermática e proteômica do plasma seminal - Cursino, Marina Suzuki [UNESP] (2014)
Brazilian gray deers are represent by two species: Gray brocket deer (Mazama gouazoubira) and Amazonian brocket deer (Mazama nemorivaga). They belong to genus Mazama, but there are genetic evidence to separate them into two different genera. To contribute to this discution about Mazama taxonomic complexity, we decide to characterize and describe the seminal plasma, of these species, in detail. We performed multivariate analisis to compare sperm morphometry data and identify the main differences between two species. We also used two-dimensional electrophoresis SDS-PAGE techniques and mass spectrometry ESI-Q TOF to compare the constitution of seminal plasma. As result, we found important differences on dimension and shape of the head sperm, being area and width the main variables that differentiate them. Using discriminant analysis, we properly separate them into two groups of species, M. gouazoubira and M. nemorivaga. Comparing the protein profile of the seminal plasma, we observed differences in the distribution of spots, and were identified different groups of proteins in seminal plasma of the distinct species. These results demonstrated that M. gouazoubira and M. nemorivaga have significant differences in the semen characteristics that reinforce the hypothesis that these two species may be separated into two new genera